The THERAPEUTIC POTENTIAL: UNDARIA PINNATIFIDA AND MORINGA OLEIFERA EXTRACTS AS MODULATORS OF ADIPOGENESIS IN 3T3-L1 ADIPOCYTES - SAI KALYANI YOGINI C; GNANESWARI K; CH KUMARI CHITTURI M (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objectives: The objectives of the study are to investigate the effects of ethanolic extract of Undaria pinnatifida (UPEA) and methanolic extract of Moringa oleifera (MOM), alone and in combination, on the differentiation and viability of 3T3-L1 pre-adipocytes. Methods: 3T3-L1 pre-adipocytes were treated with varying concentrations of UPEA, MOM, and their 1:1 combination. The impact on pre-adipocyte differentiation was assessed by measuring lipid accumulation. Cell viability was determined using a standard viability assay to evaluate cytotoxicity across a range of concentrations. Results: UPEA and MOM, individually and in combination, reduced lipid accumulation in 3T3-L1 cells in a dose-dependent manner, thereby inhibiting differentiation into adipocytes. The combination treatment (1:1 ratio) demonstrated similar efficacy in reducing differentiation. Viability assays revealed minimal cytotoxic effects, with cell viability ranging from 89% to 99% across all tested concentrations. Conclusion: UPEA, MOM, and their combination exhibit potent anti-adipogenic effects while maintaining low cytotoxicity in 3T3-L1 pre-adipocytes. These findings suggest their potential as therapeutic agents for conditions related to adipogenesis, warranting further studies on their biological activities and therapeutic mechanisms.